Practical time series - Janacek, Gareth (Arnold texts in statistics, 2001)
"The study of time ordered data is an important branch of statistics, with applications as diverse as medicine, engineering and economics. The author has written a practical textbook on this subject, with readers encouraged to use the methods described on their own data. Practical Time Series is an essential text for senior undergraduates and postgraduates studying or using time series analysis. It covers a broad spectrum of models, from ARIMA models to state space models and the Kalman filter. The estimation problem and the frequency domain are also covered, although again the emphasis is on practical applications rather than on theory."